(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food waste accounts for roughly one third of the food produced by the global food system. Food waste occurs throughout the food chain, from the farm to the plate. One billion tons of food are thought to be wasted annually. This wasted food is worth more than a trillion dollars. There are numerous reasons why food wastage occurs. This paper will explore the major reasons of food wastage and solution to that problem. An innovative solution that is emerging to address this problem is ‘upcycled food’. Food that would otherwise be thrown away is transformed into new, often healthier products through upcycling. Physical or chemical methods are used to accomplish this. This paper suggests that upcycling is a novel solution with an economic benefit to the global problem of food wastage.